(untitled) (AYUSHDHARA, 2017)
Arditavata is a disease where Mukhasankocha, Vakrata of Nasa, Bhru, Akshi, Lalata, Hanu etc, will be seen. Mouth deviation, Deafness etc are the symptoms of Bell’s palsy. The treatments like Panasapatra, Ksheeradhuma and Ekangaveeraras has been tried on Ardita. To highlight its mode of action accurately the Pharmacological analysis and HPTLC Study on the same helps in proper understanding and interpretation of drug action. This article enlightens about the Pharmacological analysis and HPTLC Study of Ekanagaveerars, Balamulakwatha churna, Ksheerabalataila and Panasapatra. As per the Analysis reports the presence of Carbohydrates, Steroids, Alkaloids, Flavonoids and Glycosides etc is positive. The pharmacologically active elements like carbohydrate, alkoloid and flavanoids are both Alcohol and water soluble whereas the others like steroids and glycosides are alcohol soluble extracts. Phytochemical Analysis of Panasapatra Choorna are both Water and alcohol soluble. Proteins, Tannins, triterpenoids and flavanoids are water soluble. Steroids alone are only alcohol soluble. The presence of these elements in the final product is directly proportional to the biological activity expressed by the product. With this in mind the Qualitative analysis of the final product holds good. By understanding of different active principles present in different formulation helps in explaining their mode of action scientifically.